New Insights and Advances in Pathogenesis and Treatment of Very Early Onset Inflammatory Bowel Disease - Li, Qi-Qi; Zhang, Hui-Hong; Dai, Shi-Xue (Frontiers in Pediatrics, 2022)
Very early onset inflammatory bowel disease (VEO-IBD) is characterized by multifactorial chronic recurrent intestinal inflammation. Compared with elderly patients, those with VEO-IBD have a more serious condition, not responsive to conventional treatments, with a poor prognosis. Recent studies found that genetic and immunologic abnormalities are closely related to VEO-IBD. Intestinal immune homeostasis monogenic defects (IIHMDs) are changed through various mechanisms. Recent studies have also revealed that abnormalities in genes and immune molecular mechanisms are closely related to VEO-IBD. IIHMDs change through various mechanisms. Epigenetic factors can mediate the interaction between the environment and genome, and genetic factors and immune molecules may be involved in the pathogenesis of the environment and gut microbiota. These discoveries will provide new directions and ideas for the treatment of VEO-IBD.